(untitled) (Swiss Medical Weekly, 2014)
In his 1966 monograph “Charcot joints”, Sidney N. Eichenholtz (1909–2000) described “three well defined stages … in the course and development of a Charcot joint”, based on plain X-rays of 68 patients. Since then, medical imaging has advanced very much: computed tomography and magnetic resonance imaging (MRI) scans exceed plain X-ray by far in detecting foot fractures and other injuries. The earliest, nondeforming, X-ray-negative inflammatory stage of the acute Charcot joint of the diabetic foot can be visualised only by use of MRI. This stage, which Eichenholtz evidently failed to recognise, will heal without significant arthropathy, if treated in time. By contrast, the stages considered by Eichenholtz inevitably result in major arthropathy and foot deformity. Hence, superseding the Eichenholtz classification is overdue. We propose an MRI-based classification comprising two severity grades (0 and 1, according to absence/presence of cortical fractures) and two stages (active/inactive, according to presence/absence of skeletal inflammation).